Implication of Scaffolding Technique for Impactful Communication in English - Ms. Riddhiben Chandubhai Chauhan (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Without communication, living is impossible, and anyone can make their life easier through communication. A language is a tool used by people to interact with one another. An individual will be able to solve every problem on their own if they acquire effective communication skills. The majority of people in this country are not able to speak English fluently, even though it is taught as a second language or as a subject in India. As a result, people are familiar with the English language and they can write it but most of the people are not able to speak fluently in the English language. As a result, ESL students find it very challenging to communicate in English. In this situation, as a teacher, you should support your pupils' ability to communicate in the classroom. The teacher must help the students improve their communication skills by using the scaffolding technique. Through pair and group work, the instructor must actively support the students' development of communication skills in the classroom. Therefore, the scaffolding technique is very important for students' development of communication skills. Students can actively participate in the teaching-learning process by using scaffolding to create a supportive learning environment. Scaffolding helps the learners in developing their The Zone of Proximal Development (ZPD), where students experience a supportive learning environment and also take a more active role in their learning.